Increasing Efficiency of Cutting Process Thai Enterprises Kanom (Krayasart) of Small Enterprises Kanom Thai Ban Tak - คำบรรลือ ชยันต์; พรไพรเพชร ธันย์นรี; วงษ์ปู่ ไกรสร (RMUTL Engineering Journal, 2019)
The objective of this project is to reduce the time and fatigue in the process of cutting Krayasart (a type of Thai dessert) for small enterprises Kanom Thai Ban Tak. Traditionally, this process was done by hand by the enterprise members, most of which were the elderly people. We applied the ECRS principle by using S (Simpilfy) to improve work process in designing the equipment, and using the mechanical principle to improve ease of use and maintenance to make it suitable for small businesses and low cost for the instruction. The result revealed that Krayasart cutting time was greatly reduced. Before the improvement, it took 6 minutes per piece (126 minutes per 34 kilogram) whereas after the improvement, the cutting time was 0.5 minutes (10.5 minutes per 34 kilogram) which showed that after improvement, the equipment was able to reduce cutting time by 5.5 minutes per piece (115.5 minutes per 34 kilogram). As a result, the equipment can increase the efficiency of the cutting process by 96.1%